Multicriteria decision making to assess waste to energy in Indonesia - Murdiyati, Sari; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2018)
Abstract. Indonesia’s population has risen in the last 35 years, as consequences this has led an increase in the volume of domestic waste. Waste is complex problems that related many stakeholders, however, the waste problem can be resolved by integrated waste management.  In the upstream level, waste is managed by Reduce, Reuse, Recycle activity. In the downstream level, waste is converting into energy. In order to accelerate the waste reduction in several urban cities by thermal technology, Presidential Regulation was issued in 2016, but there was a lawsuit against the regulation.   The final goal of this research is to select waste to energy technology from five alternatives, sanitary landfill, anaerobic digestion, gasification, incineration, pyrolysis. The method in this research is Analytical Hierarchy Process (AHP) consisted of Pairwise Comparison and Simple Multi-Attribute Rating Technique (SMART) to get priority of waste to energy technology in Indonesia. The expert has selected their priority in numerical scale then synthesis using the verbal weighting.  In criteria level, Technical criteria have the highest value, followed by Environmental.  In the sub-criteria level, financial feasibility has the highest value, followed by waste volume reduction. The priority of selected technology is 1) incineration; 2) Gasification; 3) Anaerobic digestion; 4) Sanitary landfill; 5) Pyrolysis.  Keywords : waste to energy, AHP, technical criteria, financial feasibility, inceneration.